Efficiency and power upgrade at the aged lignite-fired power plant by flue gas waste heat utilization: High pressure versus low pressure economizer installation. (15th November 2019) - Stevanovic, Vladimir D.; Petrovic, Milan M.; Wala, Tadeusz; Milivojevic, Sanja; Ilic, Milica; Muszynski, Slawomir
Abstract: A substantial potential exists for the recovery of flue gas waste heat at aged coal-fired power plants. High and low pressure economizers (HPE, LPE) can be applied for this purpose. Two cases of the feedwater supply to the HPE are considered: a supply of the "cold" feedwater taken from the feedwater pump discharge line and a supply of the "hot" feedwater taken after high pressure heaters. The LPE is fed by condensate taken from the low pressure condensate line. The heat transfer area of economizers is equal in all cases. The heat transfer rate of the LPE is maximized by the lowest possible condensate temperature at the economizer inlet, which is limited by the acid dew point temperature. The power upgrade by the HPE fed with the "cold" feedwater is by 2.5 times higher than in case with the LPE. The plant efficiency upgrade by the LPE is by 20% higher than in case with the HPE fed with "cold" feedwater. The HPE fed with the hot feedwater is not competitive. The presented overall benefits achieved by the HPE fed with the cold feedwater justify its implementation at the aged 620 MWe power plant. Highlights: Big potential for the flue gas waste heat recovery at aged coal-fired power plants. Plant retrofits with high and low pressure economizers (HPE, LPE) are compared. Ratio of power upgrades by HPE and LPE is about 2.5. Plant efficiency upgrade by LPE is by 20% higher than by HPE. HPE is installed at the aged power plant due to overall benefits.